Solvents, CO2 and biopolymers: Structure formation in chitosan aerogel. (1st November 2020) - Takeshita, Satoru; Sadeghpour, Amin; Sivaraman, Deeptanshu; Zhao, Shanyu; Malfait, Wim J.
Graphical abstract: Highlights: Effect of solvent systems on chitosan gel shrinkage and aerogel properties. SAXS identifies the step during which the gel/aerogel structure forms (solid phase). The structure can form at any synthesis step, including supercritical drying. New concept of aerogel structure control using solvent–polymer affinity. Abstract: The functionality of biopolymer aerogels is inherently linked to its microstructure, which in turn depends on the synthesis protocol. Detailed investigations on the macroscopic size change and nanostructure formation during chitosan aerogel synthesis reveal a new aspect of biopolymer aerogels that increases process flexibility. Formaldehyde-cross-linked chitosan gels retain a significant fraction of their original volume after solvent exchange into methanol (50.3 %), ethanol (47.1 %) or isopropanol (26.7 %), but shrink dramatically during subsequent supercritical CO2 processing (down to 4.9 %, 3.5 % and 3.7 %, respectively). In contrast, chitosan gels shrink more strongly upon exchange into n -heptane (7.2 %), a low affinity solvent, and retain this volume during CO2 processing. Small-angle X-ray scattering confirms that the occurrence of the volumetric changes correlates with mesoporous network formation through physical coagulation in CO2 or n -heptane. The structure formation step can be controlled by solvent–polymer and polymer–drying interactions, which would be a new tool to tailor the aerogel structure.